2022
DOI: 10.23969/trikonomika.v21i1.5085
|View full text |Cite
|
Sign up to set email alerts
|

Financial Distress, Dividend Policy, Rgec and Earning Per Share

Abstract: This study aims to examine and analyze the effect of Financial Distress, Dividend Policy and RGECon Firm Value with EPS as the intervening variable. This research is explanatory in nature and employs a quantitative descriptive method. The data utilized was gathered from the annual financial reports of commercial banks in Indonesia from 2012 to 2018, with a sample size of 23 bank. The collected data was then analyzed using SEM (Structural Equation Model) and the PLS3 Program. According to the findings of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The debt/equity ratio significantly moderates the association between financial distress and dividend payout decisions of banks Yes - decision-making process of banks' dividend payout policy [62,26,56,17,33,21,49,6]. However, as per our findings of positive and linear association among distress and dividends, it is interpreted that whenever a company faces financial difficulty, they opt to give a reasonable amount of dividends to decrease the panic level among investors.…”
Section: Comparison With Earlier Workmentioning
confidence: 52%
See 2 more Smart Citations
“…The debt/equity ratio significantly moderates the association between financial distress and dividend payout decisions of banks Yes - decision-making process of banks' dividend payout policy [62,26,56,17,33,21,49,6]. However, as per our findings of positive and linear association among distress and dividends, it is interpreted that whenever a company faces financial difficulty, they opt to give a reasonable amount of dividends to decrease the panic level among investors.…”
Section: Comparison With Earlier Workmentioning
confidence: 52%
“…Coffinet et al [20] posit that in the event of financial challenges, businesses may opt to decrease their dividend payout ratio and corresponding disbursements. Widagdo and Sa'diyah [62] find that financial distress does not influence the earnings per share of investors in Indonesian banks. Reddemann et al [49] found that the European insurance sector suggested dividend cuts to preserve capital during the financial crisis.…”
Section: Financial Distress and Dividend Distributionmentioning
confidence: 95%
See 1 more Smart Citation
“…Berbeda dengan pendapat Saputra dkk (2021) yang menyatakan bahwa ukuran perusahaan tidak berpengaruh terhadap nilai perusahaan. Penelitian yang dilakukan Anggraini dkk (2021) berpendapat bahwa inancial distress berpengaruh terhadap nilai perusahaan, berbeda dengan pendapat Widagdo (2022) menyatakan bahwa inancial distress tidak berpengaruh terhadap nilai perusahaan.…”
Section: Pendahuluanunclassified
“…DPR is mostly used to measure the percentage of cash dividends given by the company to shareholders on the earnings per share generated in the accounting period. The more the dividend payout ratio set by the company, the more dividends will be distributed to shareholders, while the company has less funds for long-term funding (Widagdo & Sa'diyah, 2022). The formula that will be used to measure the Dividend Payout Ratio is as follows:…”
Section: Literature Reviewmentioning
confidence: 99%